Engineering Entangled Photons for Transmission in Ring-Core Optical Fibers - Cañas, G.; Gómez, E. S.; Baradit, E.; Lima, G.; Walborn, S. P. (Frontiers in Physics, 2021)
The capacity of optical communication channels can be increased by space division multiplexing in structured optical fibers. Radial core optical fibers allows for the propagation of twisted light–eigenmodes of orbital angular momentum, which have attracted considerable attention for high-dimensional quantum information. Here we study the generation of entangled photons that are tailored made for coupling into ring core optical fibers. We show that the coupling of photon pairs produced by parametric down-conversion can be increased by close to a factor of 3 by pumping the non-linear crystal with a perfect vortex mode with orbital angular momentum , rather than a gaussian mode. Moreover, the two-photon orbital angular momentum spectrum has a nearly constant shape. This provides an interesting scenario for quantum state engineering, as pumping the crystal with a superposition of perfect vortex modes can be used in conjunction with the mode filtering properties of the ring core fiber to produce simple and interesting quantum states.